Contamination of bacterial extracellular vesicles (bEVs) in human urinary extracellular vesicles (uEVs) samples and their effects on uEVs study. Issue 12 (12th December 2022) - Noonin, Chadanat; Peerapen, Paleerath; Thongboonkerd, Visith
Abstract: Bacterial overgrowth is common for improperly stored urine. However, its effects on human urinary extracellular vesicles (uEVs) study had not been previously examined nor documented. This study investigated the presence of bacterial EVs (bEVs) contaminated in uEVs samples and their effects on uEVs study. Nanoscale uEVs were isolated from normal human urine immediately after collection (0‐h) or after 25°C‐storage with/without preservative (10 mM NaN3 ) for up to 24‐h. Turbidity, bacterial count and total uEVs proteins abnormally increased in the 8‐h and 24‐h‐stored urine without NaN3 . NanoLC‐ESI‐LTQ‐Orbitrap MS/MS identified 6–13 bacterial proteins in these contaminated uEVs samples. PCR also detected bacterial DNAs in these contaminated uEVs samples. Besides, uEVs derived from 8‐h and 24‐h urine without NaN3 induced macrophage activation (CD11b and phagocytosis) and secretion of cytokines (IFN‐α, IL‐8, and TGF‐β) from macrophages and renal cells (HEK‐293, HK‐2, and MDCK). All of these effects induced by bacterial contamination were partially/completely prevented by NaN3 . Interestingly, macrophage activation and cytokine secretion were also induced by bEVs purified from Escherichia coli . This study clearly shows evidence of bEVs contamination and their effects on human uEVs study when the urine samples were inappropriately stored, whereas NaN3 can partially/completely prevent such effects from the contaminated bEVs.